Effect of treatment condition on perovskite film for perovskite solar cell application - Ho Phuong, (Journal of Technical Education Science, 2021)
In this study, the Perovskite material CH3NH3PbI3 was prepared using two-step sequential solution deposition technique. The treatment condition for Perovskite film including dipping duration, reaction temperature and annealing temperature was studied. Crystal structure, grain size, and purity of the prepared material were examined using XRD and SEM methods. The results indicate that controlling treatment condition has a significant effect on the crystallinity and purity of Perovskite film. Under suitable condition, the obtained Perovskite material has a tetragonal structure and grain size ranges from 200 to 400 nm. The Perovskite film was then applied as a light-harvesting material in Perovskite solar cell. The device exhibits a power conversion efficiency of 5.18% with JSC of 13.6 mA cm-2, VOC of 0.83 V, and fill factor of 45.9%.